2021
DOI: 10.3390/ijerph18126248
|View full text |Cite
|
Sign up to set email alerts
|

Infection Control Knowledge, Attitudes, and Practices among Students of Public Dental Schools in Egypt

Abstract: In developing countries such as Egypt, the risk of blood-borne diseases such as human immunodeficiency virus, hepatitis B virus, and hepatitis C virus is high for healthcare workers. To evaluate infection control knowledge, attitudes and practices, as well as the associated risk of percutaneous infection among dental students, a cross-sectional study was conducted in four Egyptian public dental schools in 2016. A total of 1776 students received an anonymous questionnaire on infection control knowledge, attitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…Nesse contexto, El-saaidi et al (2021) evidenciaram que embora a maioria dos alunos tenha relatado boas atitudes e práticas para o controle de infecções, as pontuações de conhecimento foram geralmente baixas. Além disso, cerca de 60% e 38% sofreram ferimentos com agulhas e materiais cortantes nos últimos 6 meses, respectivamente, durante o treinamento clínico.…”
Section: Resultados E Discussõesunclassified
“…Nesse contexto, El-saaidi et al (2021) evidenciaram que embora a maioria dos alunos tenha relatado boas atitudes e práticas para o controle de infecções, as pontuações de conhecimento foram geralmente baixas. Além disso, cerca de 60% e 38% sofreram ferimentos com agulhas e materiais cortantes nos últimos 6 meses, respectivamente, durante o treinamento clínico.…”
Section: Resultados E Discussõesunclassified
“…Healthcare providers are at three to six times greater risk of blood-borne infections than other populations [8]. Proper Hepatitis B vaccination is the best procedure to prevent contagious transmission during dental treatments [9].…”
Section: Disscusionmentioning
confidence: 99%
“…Cluster-randomized controlled studies are needed to compare the various types of safety engineered devices for their effectiveness and cost-effectiveness, especially in low-and middle-income countries. Gopar-Nieto et al (2015) in Mexico repo-rted that sharps injuries were one of the most frequent health-care related accidents, which estimated globally those 35 million workers were at risk; in Mexico without available data for this injury types. They were associated with lack of training, instrument and procedure risk, fatigue and stress.…”
Section: Introductionmentioning
confidence: 99%
“…They recommended that focusing on NSI in the nursing curriculum and providing more protection and post-exposure intervention during clinical practice. El-Saaidi et al (2021) in Egypt reported that in developing countries, risk of bloodborne diseases such as human immuno-deficiency virus, hepatitis B virus, & hepatitis C virus was high for healthcare workers. To evaluate infection control knowledge, attitudes and practices, as well as the associated risk of percutaneous infection among dental students, a cross-sectional study was conducted in four Egyptian public dental schools in 2016.…”
Section: Introductionmentioning
confidence: 99%